Pengaruh Word Of Mouth, Kualitas Layanan, Dan Lokasi Terhadap Keputusan Pembelian (Studi Pada Queen Jilbab Jln. Tlogomas Kota Malang, Jawa Timur) - Magvira Nurul Khoyima; Nur Hidayati; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
ABSTRACTThis study aims to analyze the effect of word of mouth, service quality and location on   purchasing decisions on consumers of Ratu Jln hijab. Tlogomas Malang City, East Java. The population in this study were consumers who had or were making purchases and this sample was taken using purposive sampling technique and the total sample was 60 respondents. The data source used is primary data and the method of collection is using a questionnaire technique. The results of this study indicate that word of mouth, service quality and location influence purchasing decisions, the variable word of mouth partially has a positive and significant effect on consumer purchasing decisions of Ratu Jln hijab. Tlogomas Malang City, East Java.Keywords: word of mouth, service quality, location, purchasing decisions